How to differentiate the B.1.1.7 variant from COVID-19 in hospitalized patients? - Koç, İbrahim and Gullu, Yusuf Taha (The European Research Journal, 2022)
Objectives: Little is known about COVID-19 and less about the B.1.1.7. There is a need for clinical information and tests to help doctors deal with the pandemic. This study aimed to investigate clinical and laboratory differences between hospitalized non-variant COVID-19 and the B.1.1.7 variant. Methods: Data of 173 hospitalized non-variant COVID-19 and 176 B.1.1.7 variants were retrospectively investigated. D-dimer monocyte ratio (DMR) and ferritin monocyte ratio (FMR) values were calculated by dividing D-dimer and ferritin levels to monocyte count, respectively. Monocyte eosinophil ratio (MER) was obtained by dividing monocyte count by eosinophil levels. Results: Clinical stay, intensive care unit (ICU) stay, and severe disease rates were found to be higher in the non-variant COVID-19. Eosinophil and basophil levels remained lower, whereas ferritin, FMR, and MER were more elevated in the same group. On ROC analysis, areas under the curve (AUC) of ferritin and FMR were found as 0.7 (p = 0.001) and 0.75 (p = 0.001), respectively. Conclusions: The present study revealed that the B.1.1.7 variant had milder clinical manifestations, shorter clinic and ICU stay, and less severe disease rates than the non-variant COVID-19. Higher levels of ferritin, FMR, and MER may indicate the B.1.1.7 variant.